Effect of microwave disinfection on the bond strength of denture teeth to acrylic resins - Ribeiro, Roberta Chuqui [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Pavarina, Ana Claudia [UNESP] (Elsevier B.V., 2008)
During microwave disinfection, the dentures are exposed to water at high temperature and this may affect the bond between the denture teeth and the acrylic resin from which dentures are made. In this study, a shear test was used to evaluate the effect of microwave disinfection (650W/6 min) on the bond strength of two types of denture teeth to three acrylic resins, with different polymerization methods. The specimens were submitted to the shear tests (0.5 mm/min) after: immersion in water (37 degrees C) for 48 h or 8 days (controls); two or seven cycles of microwave disinfection (test groups). Data (MPa) were analyzed using three-way ANOVA and Tukey HSD test (alpha = 0.05). Microwave disinfection did not adversely affect the bond strength of all tested materials with the exception of QC-20 bonded to SR Vivodent PE, for which a significant reduction was recorded after seven cycles of irradiation. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: interfaces; adhesion by chemical bonding; fracture; acrylic resins